Educational attainment and mortality in schizophrenia. (18th February 2022) - Tesli, Martin; Degerud, Eirik; Plana‐Ripoll, Oleguer; Gustavson, Kristin; Torvik, Fartein Ask; Ystrom, Eivind; Ask, Helga; Tesli, Natalia; Høye, Anne; Stoltenberg, Camilla; Reichborn‐Kjennerud, Ted; Nesvåg, Ragnar; et al.
Abstract: Background: Individuals suffering from schizophrenia have a reduced life expectancy with cardiovascular disease (CVD) as a major contributor. Low educational attainment is associated with schizophrenia, as well as with all‐cause and CVD mortality. However, it is unknown to what extent low educational attainment can explain the increased mortality in individuals with schizophrenia. Aim: Here, we quantify associations between educational attainment and all‐cause and CVD mortality in individuals with schizophrenia, and compare them with the corresponding associations in the general population. Method: All Norwegian citizens born between January 1, 1925, and December 31, 1959, were followed up from January 1, 1990, to December 31, 2014. The total sample included 1, 852, 113 individuals, of which 6548 were registered with schizophrenia. We estimated hazard ratios (HR) for all‐cause and CVD mortality with Cox models, in addition to life years lost . Educational attainment for index persons and their parents were included in the models. Results: In the general population individuals with low educational attainment had higher risk of all‐cause (HR: 1.48 [95% CI: 1.47–1.49]) and CVD (HR: 1.59 [95% CI: 1.57–1.61]) mortality. In individuals with schizophrenia these estimates were substantially lower (all‐cause: HR: 1.13 [95% CI: 1.05–1.21] and CVD: HR: 1.12 [95% CI: 0.98–1.27]). Low educational attainment accounted for 3.28 (3.21–3.35) life years lost in males and 2.48 (2.42–2.55) years in females in the general population, but was not significantly associated with life years lost in individuals with schizophrenia. Results were similar for parental educational attainment. Conclusions: Our results indicate that while individuals with schizophrenia in general have lower educational attainment and higher mortality rates compared with the general population, the association between educational attainment and mortality is smaller in schizophrenia subjects than in the general population.